Economic Structure and Growth in the Brussels Metropolitan Area - Didier Baudewyns (Brussels Studies, 2007)
The article opens with a study of developments in the Brussels Metropolitan economy over the past twenty years in terms of economic growth and local specialisation in production. It then reviews recent empirical studies of the link between local economic structure (in terms of production specialisation, sectoral diversity, and competition) and local economic growth in Belgium and the rest of Europe. The author deduces therefrom the recommendation that no sectoral policy should be implemented if it is detrimental to the diversity of the Brussels Region’s economic fabric. This analysis is based in particular on a new indicator of total local diversity computed from sectoral employment data by Belgian statistical district for 1996‑2003.